Forcibly displaced persons and mental health: A survey of the experiences of Europe-wide psychiatry trainees during their training. (February 2023) - Frankova, Iryna; Scheeres, Karl; Menculini, Giulia; Cikrikcili, Uğur; Matei, Ioan-Costin; Fellinger, Matthäus; Riboldi, Ilaria; Uzer-Kremers, Laura; Küey, Levent
Many European countries have seen increasing refugee populations and asylum applications over the past decade. Forcibly displaced persons (FDPs) are known to be at higher risk of developing mental disorders and are in need of specific care. Thus, specific training for mental health professionals is recommended by international health organizations. The aim of this exploratory study was to assess the experience of clinical work with FDPs among psychiatric trainees in Europe and Central Asia as well as their interest and specific training received on this topic. An online questionnaire was designed by the Psychiatry Across Borders working group of the European Federation of Psychiatric Trainees (EFPT) and was distributed via email through local networks among European trainees from 47 countries between March 2017 and April 2019. Answers of 342 psychiatric trainees from 15 countries were included in the survey analysis. A majority of trainees (71%) had had contact with FDPs in the last year of their clinical work. Although three-quarters expressed a strong interest in the mental health of FDPs, only 35% felt confident in assessing and treating them. Specific training was provided to 25% of trainees; of this subset, only a quarter felt this training prepared them adequately. Skills training on transcultural competencies, post-traumatic stress disorder, and trauma management was regarded as essential to caring for refugees with confidence. Although psychiatric trainees are motivated to improve their skills in treating FDPs, a lack of adequate specific training has been identified. The development of practical skills training is essential. International online training courses could help meet this pressing need.